A novel mind‐set in primate experimentation: Implications for primate welfare. Issue 4 (29th November 2021) - Tramacere, Antonella; Iriki, Atsushi
Abstract: We emphasize the importance of studying the primate brain in cognitive neuroscience and suggest a new mind‐set in primate experimentation within the boundaries of animal welfare regulations. Specifically, we list the advantages of investigating both genes and neural mechanisms and processes in the emergence of behavioral and cognitive functions, and propose the establishment of an open field of primate research. The latter may be conducted by implementing and harmonizing experimental practices with ethical guidelines that regulate (1) management of natural parks with free‐moving populations of target nonhuman primates, (2) establishment of indoor‐outdoor labs for both system genetics and neuroscience investigations, and (3) hotel space and technologies which remotely collect and dislocate information regarding primates geographically located elsewhere.